Writing a narrative text in Writing for Information and Enjoyment Class utilising Project Based Learning - Yeni Rahmawati; Khusnul Khatimah; Dzul Rachman (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
The objective of this study was to examine the impact of project-based learning (PBL) on enhancing students' proficiency in narrative writing. The study employed a mixed methods approach, specifically utilising a quasi-experimental design and incorporating writing test and interview as a data collection method.The total sampel was 54 students in experiment and control group. The utilisation of Project-based Learning in the composition of narrative texts yielded more favourable outcomes in enhancing students' writing proficiency, as evidenced by the analysis of data. It has been demonstrated that the value of the t-statistic exceeded the critical value. The results indicated that 44% of students demonstrated improvement according to the established criteria following the intervention. Based on the findings from the interview session, it was observed that students who underwent Project-based Learning (PBL) expressed a sense of satisfaction. This can be attributed to the fact that PBL proved to be effective in assisting students in attaining their writing objectives by the conclusion of the academic term.